A novel colorimetric fluorescence sensor for Fe3+ based on quinoline Schiff base. (7th July 2017) - Li, Bin; Tian, Jianfei; Zhang, Dan; Tian, Fuli
Abstract: A novel fluorescent sensor bearing a quinoline and an anisidine moiety has been developed for highly selective detection of Fe 3+, which shows photo‐induced electron transfer (PET) behavior induced by Fe 3+ . Binding of Fe 3+ to the sensor induced the electron of C = N group transfer from quinoline to iron, the result exhibits fluorescent enhancement. With the features of easy synthesis, simple structural skeleton and excellent sensing ability, the newly synthesized chemosensor also applied as a highly selective fluorescent probe in complex samples containing various competitive metal ions. The probe could fulfill various needs in biological and environmental fields.